SNAP25 differentially contributes to Gi/o-coupled receptor function at glutamatergic synapses in the nucleus accumbens - Manz, Kevin M.; Zepeda, José C.; Zurawski, Zack; Hamm, Heidi E.; Grueter, Brad A. (Frontiers in Cellular Neuroscience, 2023)
The nucleus accumbens (NAc) guides reward-related motivated behavior implicated in pathological behavioral states, including addiction and depression. These behaviors depend on the precise neuromodulatory actions of Gi/o-coupled G-protein-coupled receptors (GPCRs) at glutamatergic synapses onto medium spiny projection neurons (MSNs). Previous work has shown that discrete classes of Gi/o-coupled GPCR mobilize Gβγ to inhibit vesicular neurotransmitter release via t-SNARE protein, SNAP25. However, it remains unknown which Gαi/o systems in the NAc utilize Gβγ-SNARE signaling to dampen glutamatergic transmission. Utilizing patch-clamp electrophysiology and pharmacology in a transgenic mouse line with a C-terminal three-residue deletion of SNAP25 (SNAP25Δ3) weaking the Gβγ-SNARE interaction, we surveyed a broad cohort of Gi/o-coupled GPCRs with robust inhibitory actions at glutamatergic synapses in the NAc. We find that basal presynaptic glutamate release probability is reduced in SNAP25Δ3 mice. While κ opioid, CB1, adenosine A1, group II metabotropic glutamate receptors, and histamine H3 receptors inhibit glutamatergic transmission onto MSNs independent of SNAP25, we report that SNAP25 contributes significantly to the actions of GABAB, 5-HT1B/D, and µ opioid receptors. These findings demonstrate that presynaptic Gi/o-coupled GPCRs recruit heterogenous effector mechanisms at glutamatergic synapses in the NAc, with a subset requiring SNA25-dependent Gβγ signaling.